IL-32 expression associated with lymph vessel invasion in intestinal type of gastric cancer - Pavlović Mladen; Jurišević Milena; Gajović Nevena; Mitrović Slobodanka; Jovanović Milan; Radosavljević Gordana; Pantić Jelena; Radovanović Dragče; Arsenijević Nebojša; Jovanović Ivan (Vojnosanitetski Pregled)
Background/Aim. Gastric cancer (GC) is fourth most frequent malignant tumor worldwide, frequently diagnosed at advanced stages with poor prognosis. The aim of study was to determine expression of interleukin (IL)-32, proinflammatory and angiogenic mediators in the tumor, peritumor and healthy tissue, in patients with intestinal gastric cancer and the relationship with the disease severity. Methods. The tissue samples of intestinal type of the tumor of 60 patients with GC were analyzed. Expression of IL-32, vascular endothelial growth factor (VEGF), IL-17 and CD31 were measured by immunohistochemistry. Results. IL-32, VEGF and IL-17 expression as well as microvascular density (MVD) were diminished in adjacent tumor tissues compared with the tumor ones. Further, more intense expression of IL-32 and VEGF and enhanced MVD were noticed in patients with severe (TNM stages III and IV) and more progressive GC (lymph vessel invasion). Conclusion. Higher expression of IL-32, VEGF and intense MVD in the tumor tissue of GC patients with detectable lymph vessel invasion may be considered as a sign of the tumor’s malignant progression. This indicates a protumorogenic and proangiogenic role of IL-32 in biology of intestinal type of gastric cancer.